Longitudinal analysis of brain functional connectivity and its association with clinical assessment in depressed patients using resting state fMRI - Vincent Chin-Hung Chen; Zi-You Qiu; Yuan-Hsiung Tsai; Gigin Lin; Yi-Peng Eve Chang; Jun-Cheng Weng (Scientific Reports)
Abstract Suicidal ideation (SI) is an important predictor of suicide attempts, yet SI is difficult to predict. It is also important to understand the associations between network function and SI (or the absence of suicidal ideation, NS) in patients with depression. We recruited 83 participants and divided them into four groups: 25 healthy controls (HCs), 27 depressed patients without suicidal ideation (NS), 18 depressed patients with suicidal ideation (SI), and 13 depressed patients whose SI was converted to NS (improved). All subjects underwent resting-state fMRI at baseline (TP1) and one year later (TP2) after receiving therapy. Patients also underwent four clinical assessments that yielded scale scores. We used the mean amplitude of low-frequency fluctuations (mfALFF) and mean regional homogeneity (mReHo) to compare the function of each brain region at TP1 and TP2. Graph theoretical analysis and network-based statistic analysis were performed to assess changes in connectivity from TP1 to TP2. Multiple regression analysis was also used to examine the association between brain function alterations and clinical assessment changes in each group. Post-treatment, significant functional activity differences were observed: in the cuneus and cingulate for NS; inferior parietal lobule and frontal regions for SI; and parahippocampus and thalamus for the improved group. Increased functional interconnections were noted among frontal, occipital, and temporal lobes. Several connectivity changes correlated with clinical assessment variations (HAM-D, HADS-A, BSS, RRS) across groups, including the caudate, precuneus, and cingulate. We deliberated on the impact of treatment on distinct cerebral regions within the NS and SI cohorts across various conditions. Within the improved group, discernible alterations in brain function following treatment amelioration were identified among the same cohort of individuals, encapsulating modifications in both pathological conditions and cerebral functionality. These findings contribute to our understanding of the neural correlates of depressive disorder and suicidal ideation and highlight the potential impact of therapeutic interventions on brain function in these populations.